2013
DOI: 10.2478/vjbsd-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Rapeseed for Biofuels Production in the EU

Abstract: Biofuels production has risen rapidly in the past decade. Growing tendency can be expected in the future if national governments will continue in achievement of higher share of ‘green energy’. Diversification and self-sufficiency in energy and environmental aspects should underpin national and international policy. Consumption of biofuels in the transport sector has been significantly increasing since 2000. Biofuels produced in the EU are mostly first-generation biofuels, mainly produced from agricultural raw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 2 publications
(1 reference statement)
0
19
0
Order By: Relevance
“…Both rapeseed and soy beans have a growth rate less than one year [122]. Furthermore, both have a high yield, which is one reason they are cultivated for producing biofuels [123]. Thus, the corresponding indicator value is zero, which means that for both plants limitations to availability due to replenishment are not a limiting factor.…”
Section: Physical Constraintsmentioning
confidence: 99%
“…Both rapeseed and soy beans have a growth rate less than one year [122]. Furthermore, both have a high yield, which is one reason they are cultivated for producing biofuels [123]. Thus, the corresponding indicator value is zero, which means that for both plants limitations to availability due to replenishment are not a limiting factor.…”
Section: Physical Constraintsmentioning
confidence: 99%
“…Production of biodiesel by trans-esterification of vegetable oils is currently the primary source of biodiesel. The most widely used input material for biodiesel production in the EU is rapeseed oil made from rapeseed, which accounts for the production of biodiesel in the range of 57% to 70% (Zentková and Cvengrošová 2013). Therefore, HEAR oil bring an idea to use as biodiesel for their characteristic properties with very high number of carbon atoms (C22:1) and potentiality to produce more energy.…”
Section: Rapeseed Oil As Biodieselmentioning
confidence: 99%
“…The rest of the production of biodiesel coming from waste materials is estimated to make 2% (USDA 2011). Zentková and Cvengrošová (2013) reported that the ever increasing demand of biodiesel leads to an increase in production and acreage of rapeseed as an input for biodiesel production. Production of biodiesel represents new opportunities for farmers for the placement of their production.…”
Section: Rapeseed Oil As Biodieselmentioning
confidence: 99%
“…Rapeseed meal is a by-product of vegetable oil production [Kreps et al, 2014]. In recent years, a steady increase in the generation of rapeseed meal worldwide is observed due to enhanced interest in rapeseed oil as a stock for biofuel production [Zentková & Cvengrošová, 2013]. Its quantity may reach up to 48% of the rape seeds used [Ivanova, 2012].…”
Section: Introductionmentioning
confidence: 99%